1993
DOI: 10.1080/03014223.1993.10422865
|View full text |Cite
|
Sign up to set email alerts
|

Sex pheromones of two New Zealand tortricid moths,Cnephasia jactatanaandMerophyas leucaniana

Abstract: The sex pheromones of two endemic New Zealand tortricid species were investigated. Females of the first species, Cnephasia jactatana, a pest of kiwifruit, were found to produce (Z)-IItetradecenyl acetate (Zll-14:0Ac) in their sex pheromone gland. When tested in the field, this compound on its own elicited significant catches of male C. jactatana. However, the addition of even very small amounts (0.3%) of the geometric isomer, (E)-II-tetradecenyl acetate (E 11-14:0Ac), to Z 11-14:0Ac virtually suppressed trap c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1994
1994
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…Local identifications of sex pheromones for New Zealand in the 1980s primarily focussed on the native torticid leafrollers that were pests of horticulture and related species (Galbreath et al 1985;Young et al 1985;Foster & Roelofs 1987;Foster et al 1990;Clearwater et al 1991;Foster & Dugale 1991;Foster et al 1993). A lack of commercial availability led to the development of pheromone lures and trap products for a range of horticultural pest species and sales from the late 1980s by the then government organisation, the Department of Scientific and Industrial Research.…”
Section: Pheromone Identification For Trapping and Mating Disruptionmentioning
confidence: 99%
“…Local identifications of sex pheromones for New Zealand in the 1980s primarily focussed on the native torticid leafrollers that were pests of horticulture and related species (Galbreath et al 1985;Young et al 1985;Foster & Roelofs 1987;Foster et al 1990;Clearwater et al 1991;Foster & Dugale 1991;Foster et al 1993). A lack of commercial availability led to the development of pheromone lures and trap products for a range of horticultural pest species and sales from the late 1980s by the then government organisation, the Department of Scientific and Industrial Research.…”
Section: Pheromone Identification For Trapping and Mating Disruptionmentioning
confidence: 99%
“…E. postvittana was also obtained as dried cadavers from laboratory parasitised larvae (7-14 days postemergence of parasitoid). Field populations of all species, with the exception of P. notophaea(which is rare in orchards), were obtained from pheromone-trapped male moths (Suckling and Shaw 1990;Foster et al 1993), stored frozen on the sticky bases and then scraped off immediately prior to use.…”
Section: Leafrollersmentioning
confidence: 99%
“…Because C. jactatana is not present in any of the countries that import New Zealand horticultural crops, it is considered a quarantine pest (Steven 1990). Foster et al (1993) identified the female sex pheromone for C. jactatana, and Ochieng '-Odero & Singh (1992) and Jiménez-Pérez & Wang (2001) have provided useful information on the biology of this species. However, there has been no report on its adult activity patterns, making the development of behaviour-based and environmentally friendly control tactics difficult.…”
Section: Introductionmentioning
confidence: 99%